Una prova di abilità linguistiche per l'uscita dai percorsi di Formazione professionale - Pietro Lucisano (LED Edizioni Universitarie, 2010)
A Language Competence Test on Exiting Vocational Training Programmes This paper illustrates the methodology adopted to design and calibrate a test for measuring students' language skills at the end of the third year of vocational training courses (10th grade). The work is part of a major ISFOL study also including tests on math and strategic abilities. The test is calibrated on a judgement sample of 1046 students. It measures listening, reading comprehension, proper use of language and written composition through several tasks. This paper presents methodologies of two item analysis procedures the CTT (Classical Test Theory) and IRT (Item Response Theory) and the procedures for designing variables derived from different tasks. In particular, it presents the advantages of using the Rasch model, which is adopted for a better measuring of the latent trait «ability» and for calibrating item measures. At the end of the paper, the main results of the multivariate analysis are briefly presented. They need to be read and interpreted taking into account the characteristics of the population, its social and cultural background, which is weak in this case, and the collection of its school failures, characterizing these students' experience.